2017
DOI: 10.1177/2332649217730086
|View full text |Cite
|
Sign up to set email alerts
|

School Strictness and Education: Investigating Racial and Ethnic Educational Inequalities Associated with Being Pushed Out

Abstract: There are racial and ethnic disparities associated with school discipline practices and pushout rates. In addition, research suggests that urban schools have stricter school discipline practices and higher pushout rates. What remains unknown, however, is the relationship between racial and ethnic inequality, school discipline practices, and pushout rates across urban, rural, and suburban schools. Therefore, this study draws from the Texas Education Agency’s (TEA) Public Education Information Management System … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Additionally, the study highlighted that major urban high-poverty schools were notorious for utilizing exclusionary practices more frequently than rural districts with small percentages of students living in poverty. Varela, Peguero, Eason, Marchbanks, and Blake (2018) used seventh-grade cohort data from the Texas Academic Indicator System, the Public Education Information Management System, and the Texas Juvenile Probation Commission to examine the correlations among race/ethnicity, urbanicity, and school discipline practices and found that rural schools were less stringent than urban and suburban schools, urban schools were more lenient than suburban schools, and rural schools were less lenient than suburban schools. There is also concern regarding the extent to which school type contributes to discipline disparities.…”
Section: School Level Location and Typementioning
confidence: 99%
“…Additionally, the study highlighted that major urban high-poverty schools were notorious for utilizing exclusionary practices more frequently than rural districts with small percentages of students living in poverty. Varela, Peguero, Eason, Marchbanks, and Blake (2018) used seventh-grade cohort data from the Texas Academic Indicator System, the Public Education Information Management System, and the Texas Juvenile Probation Commission to examine the correlations among race/ethnicity, urbanicity, and school discipline practices and found that rural schools were less stringent than urban and suburban schools, urban schools were more lenient than suburban schools, and rural schools were less lenient than suburban schools. There is also concern regarding the extent to which school type contributes to discipline disparities.…”
Section: School Level Location and Typementioning
confidence: 99%
“…Students were asked if they had ever experienced any of the three forms of school punishment during the 2001–2002 academic year. Although there is research that denotes that the severity of the punishment can have distinct detrimental consequences (Rios , ; Skiba, Arredondo, and Williams ; Varela et al ), the variability of how these difference punishment practices are implemented are significant between schools (Kupchik , ; Marchbanks et al ). Therefore, as measured in prior studies utilizing the same data (Mowen ; Peguero and Bracy ), punishment is dichotomized to indicate whether or not the student was disciplined at school.…”
Section: Methodsmentioning
confidence: 99%
“…In the wake of the ubiquitous zero‐tolerance policies across U.S. public schools, research demonstrates that students of color, immigrant youth, and low‐income children are disproportionately subject to school punishment. The negative effects associated with the disparate enforcement of zero‐tolerance policies include a higher likelihood of becoming involved in the criminal justice system and having lower educational outcomes (Fabelo et al ; Marchbanks et al ; Varela et al ). We know, however, that students’ perceptions of school procedural justice can be important factors in mitigating the negative experiences of marginalized youth with the disciplinary process and their long‐term consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The partnership forged between the schools and the courts, which has been harmful and punitive to various vulnerable student populations (Mallett, 2016), has been referred to as the school-to-prison pipeline or school pathway to the juvenile system (Marsh, 2014). Through this system of exclusionary discipline practices, students can become academically disengaged and develop negative relationships with school staff that results in disciplinary issues (Varela, Peguero, Eason, Marchbanks, & Blake, 2018). Students who are excluded from school exhibit undesirable traits that schools generally perceive as troublesome (Boylan & Renzulli, 2017) and these students may find it difficult to reenter to the school upon completion of their disciplinary action.…”
Section: Conclusion/implications For Practicementioning
confidence: 99%